2022
DOI: 10.1002/pros.24423
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of gonadotrophin‐releasing hormone agonist use and cardiovascular risks: A population‐based competing‐risk analysis

Abstract: Background: Although androgen deprivation therapy has known cardiovascular risks, it is unclear if its duration is related to cardiovascular risks. This study thus aimed to investigate the associations between gonadotrophin-releasing hormone (GnRH) agonist use duration and cardiovascular risks.Methods: This retrospective cohort study included adult patients with prostate cancer receiving GnRH agonists in Hong Kong during 1999-2021. Patients who switched to GnRH antagonists, underwent bilateral orchidectomy, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…1 However, it is associated with increased cardiovascular risks, including elevated risks of cardiovascular mortality, myocardial infarction and stroke. 2,3 Nonetheless, prior studies have focussed on the first occurrence of adverse cardiovascular events, 2,4,5 and the burden of cardiovascular hospitalizations in patients with PCa receiving ADT has remained unexplored. Similarly, the long-term burden of cardiovascular mortality amongst ADT users has been underexplored.…”
mentioning
confidence: 99%
“…1 However, it is associated with increased cardiovascular risks, including elevated risks of cardiovascular mortality, myocardial infarction and stroke. 2,3 Nonetheless, prior studies have focussed on the first occurrence of adverse cardiovascular events, 2,4,5 and the burden of cardiovascular hospitalizations in patients with PCa receiving ADT has remained unexplored. Similarly, the long-term burden of cardiovascular mortality amongst ADT users has been underexplored.…”
mentioning
confidence: 99%
“…Mortality data were acquired from the linked Hong Kong Death Registry, a governmental registry of mortality data for Hong Kong citizens. CDARS and the linked Hong Kong Death Registry have been used extensively in research, and have been demonstrated to have good coding accuracy and data completeness [17] , [18] , [19] , [20] , [21] , [22] .…”
Section: Methodsmentioning
confidence: 99%
“…Mortality data were retrieved from the linked Hong Kong Death Registry, a governmental registry which records mortality data of all Hong Kong citizens. CDARS and the linked Hong Kong Death Registry have been used extensively in prior studies, and have been shown to have good coding accuracy (18)(19)(20)(21)(22).…”
Section: Data Sourcementioning
confidence: 99%
“…Nevertheless, previous studies have demonstrated good coding accuracy and data completeness in CDARS (41), and CDARS has been used extensively in research (18)(19)(20)(21)(22). Although individual adjudication of patient data was not possible due to the deidentified nature of the database, all the data was entered by treating clinicians without any involvement from any of the authors, and none of the authors had the right or authority to alter the data.…”
Section: Strengths and Limitationsmentioning
confidence: 99%